Sistem Jaringan Komunikasi dalam Pembangunan Nasional - Biryanto (Badan Riset dan Inovasi Daerah (BRIDA) Provinsi Riau, 2018)
Communication network system is a unity of the components of the nation as interconnected communication participants functionally, and has a specific purpose in social system. The purpose of the study is to discuss the role of central and local governemnt as an element in national development, and analyze the communication network system. The method used is literature study by combining communication theories, research results, and government regulations. On national development, the central governement acts as the responsible party, the compiler, and the implementer of national development assisted by local government based on distribution of government affairs. The success of national development is determined by the active role of all components, namely government (central and local), private, and community. Accelerated development can be implemented by optimizing the communication network, so that development information can be accessed quickly and accurately by all components of nation. Availability of access to development information, is expected to increase awareness, and encourage all components of nation to play an optimal role to achieve the goals of national development.